1995
DOI: 10.1507/endocrj.42.811
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Initially Undiagnosed Hypoadrenalism Presenting Inappropriate Secretion of Anti-Diuretic Hormone.

Abstract: Abstract.The case of a 55-year-old woman with inappropriate secretion of anti-diuretic hormone (ADH) is reported.Her pituitary-adrenocortical function test showed normal values on admission, but when she recovered from hyponatremia, severe panhypopituitarism became overt. Her adrenal insufficiency was considered to have been "masked" by endogenous stimulation of the hypothalamus-pituitaryadrenal axis under severe stress. One should be cautious in estimating the pituitary-adrenal function of severely ill patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thus, we were finally able to confirm that the hyponatremia was caused by hypothalamic adrenal insufficiency. Weonly found one report in the literature regarding basal adrenal levels within the normal range in adrenal insufficiency (7). Hyponatremia is one of the features in patients with hypopituitarism.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, we were finally able to confirm that the hyponatremia was caused by hypothalamic adrenal insufficiency. Weonly found one report in the literature regarding basal adrenal levels within the normal range in adrenal insufficiency (7). Hyponatremia is one of the features in patients with hypopituitarism.…”
Section: Discussionmentioning
confidence: 82%
“…15 There are several reports stating increased ADH levels in cases with hypocortisolism associated with hyponatremia. 3,16,17 Contrary to this finding, some defects in renal mechanisms were also considered. It was shown that rats with diabetes insipidus (Brattleboro rats) had impaired renal water excretion after 2 weeks of glucocorticoid depletion, suggesting ADHindependent pathways.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, virtually all hyponatremic patients with ACTH deficiency were reported to be over 50 years of age. 16,17,[20][21][22] Diederich et al 22 reported that 28 of 185 patients with hyponatremia had ACTH deficiency and only 3 of them were younger than 60 years of age. Their mean age was 68 years, which was nearly 10 years lower than with the other causes of SIADH.…”
Section: Discussionmentioning
confidence: 99%
“…After the establishment of a sensitive radioimmunoassay ofADH, there came reports demonstrating a role of ADHin hyponatremic patients with hypoadrenalism due to hypopituitarism (12,13). Serum arginine vasopressin (AVP) was inappropriately high in relation to low serum osmolality in these patients.…”
mentioning
confidence: 99%